Attitude of Beneficiary farmers towards the Service Delivery System of Agro Service Centres in Kerala, India - Yoosuf, Safna Vatakke Kandy Meethal; B Seema (Journal of Extension Education, 2023)
The attitude of farmers and other stakeholders towards farming is formed based on the way they have been treated by the agricultural extension and service delivery system. The present study was conducted among the beneficiary farmers of Agro Service Centres (ASCs) in Thrissur, Kannur and Kottayam districts of Kerala, India, representing the central, northern and southern Kerala. The sample of the study comprised 120 farmers i.e., 45 farmers from Thrissur, 45 farmers from Kannur and 30 farmers from Kottayam. The purpose of this study was to examine and understand the beneficiary farmers’ attitudes toward the Agro Service Centers’ service delivery system and to determine whether there are any appreciable differences in those attitudes between the three districts. Based on the analysis of data, it was observed that half of the respondents had a medium level of favourable attitude towards the service delivery system of Agro Service Centres. The result of Kruskal Wallis test indicated that there was significant differences in the attitude of farmer beneficiaries towards the service delivery system of Agro Service Centres among the three districts. The correlation analysis revealed that the attitude of beneficiaries towards the Agro Service Centre was positively and significantly correlated with farming experience, annual farm income, resource utilization, and change proneness and it was negatively and significantly correlated with risk orientation.